Association of actigraphy-derived circadian phase indicators with the nadir of spindle frequency - G. Horváth, Csenge; Bódizs, Róbert (Biological rhythm research, 2024)
The measurement of chronotype and circadian rhythms in polysomnography (PSG) studies is unresolved as no validated PSG markers have been published before. Data suggest that overnight changes in sleep spindle frequency (SSF) are due to a time-of-day effect, the nadir reflecting the middle of the biological night. In this study, we tested the nadir of sleep spindle frequency (NSSF) as a phase angle estimate of the circadian rhythm. The associations between NSSF, Munich Chronotype Questionnaire (MCTQ) and actigraphy-derived sleep midpoints were analysed in a healthy young adult sample (N = 31; 16 females). MCTQ sleep midpoints on workdays, furthermore all actigraphy-derived sleep midpoint metrics and the least active 5 hours were consistent with the individual differences in NSSF, highlighting the potential use of NSSF as a chronotype indicator. Although further validation is needed, these results could open new horizons in the role of PSG recordings in circadian rhythm research